JiST: an efficient approach to simulation using virtual machines - Barr, Rimon; Haas, Zygmunt J.; van Renesse, Robbert (Software, practice & experience, 2005)
Discrete event simulators are important scientific tools and their efficient design and execution is the subject of much research. In this paper, we propose a new approach for constructing simulators that leverages virtual machines and combines advantages from the traditional systems‐based and language‐based simulator designs. We introduce JiST, a Java‐based simulation system that executes discrete event simulations both efficiently and transparently by embedding simulation semantics directly into the Java execution model. The system provides standard benefits that the modern Java runtime affords. In addition, JiST is efficient, out‐performing existing highly optimized simulation runtimes. As a case study, we illustrate the practicality of the JiST framework by applying it to the construction of SWANS, a scalable wireless ad hoc network simulator. We simulate million node wireless networks, which represents two orders of magnitude increase in scale over what existing simulators can achieve on equivalent hardware and at the same level of detail. Copyright © 2005 John Wiley & Sons, Ltd.